Organizational Sustainability: Leadership Development, Resilience Organization, Community Trust, Organizational Performance - Agustian Zen (Dinasti Publisher, 2023)
The purpose of this study is to prove and strengthen the results of previous research derived from scientific articles related to the variables used in this study, The research method used is qualitative with literature studies, by proving the results of scientific articles originating from reputable international journals in accordance with the variables in this study, the variables in this study have a positive and significant influence on only one variable with less strong evidence because the findings of scientific articles are not directly as variables in the study, namely community trust with sustainability organizations, recommendations for future research for other researchers with differentiating variables that can be used, namely Corporate social responsibility, Social and environmental accounting, organizational trust, regional innovation, and public trust, innovation and satisfaction.